Speech Acts of Male and Female Language in the Novel Shaf by Ima Madani (PT. LARPA JAYA PUBLISHER, 2023)
This study aims to describe the speech acts of men and women in the novel Shaf by Ima Madani. The research is textual in nature and employs a pragmatic approach, using a descriptive method to analyze the data. The data consist of the novel's text, which contains various types of speech acts: representative, directive, expressive, commissive, and declarative. The primary source of data is the novel itself. Data collection was conducted through purchasing, reading, observing, and marking relevant passages. The analysis involved several steps, including data collection, reduction, display, conclusion, and verification. By applying this approach, the study identifies how men and women use different speech acts in various contexts within the narrative. The findings aim to provide insights into gender-based language patterns, illustrating how characters express, request, promise, or declare through speech. This study contributes to understanding the pragmatic functions of language in literary texts, showing the relationship between linguistic choices and character roles. Overall, the research highlights the diversity of speech acts in Shaf and demonstrates the effectiveness of a textual-pragmatic approach in literary analysis, offering a structured method for examining how dialogue reflects social and interpersonal dynamics in the novel.